Psychological reactance to online recommendation services - Lee, Gyudong; Lee, Won Jun (Information & management, 2009)
Adoption of online recommendation services can improve the quality of decision making or it can pose threats to free choice. When people perceive that their freedom is reduced or threatened by others, they are likely to experience a psychological reactance where they attempt to restore the freedom. We performed an experimental study to determine whether users’ expectation of personalization increased their intention to use recommendation services, because their perception of expected threat to freedom caused by the recommendations reduced their intention to participate. An analysis based on subjects’ responses after using a hypothetical shopping website confirmed the two-sided nature of personalized recommendations, suggesting that the approach and avoidance strategies in persuasive communications can be effectively applied to personalized recommendation services on the web. Theoretical and practical implications are discussed.